Designing and in Silico Analysis of PorB Protein from Chlamydia Trachomatis for Developing a Vaccine Candidate - Pourhajibagher, M.; Bahador, A. (Drug Research, 2016)
Bakground: Chlamydia trachomatis is an obligate, intracellular, gram-negative bacterium that causes sexually transmitted infections. The outer membrane protein PorB is a conserved chlamydial protein that functions as a porin and is a target for neutralizing antibodies (Abs); thus, making it important for vaccine development.Methods: We used an in silico strategy and homology modeling algorithms and focused on PorB of C. trachomatis and explained its characterization with the help of bioinformatic tools to introduce it as a candidate for novel drug and vaccine design. In this study, physicochemical characterization, secondary and 3D structure, and functional site prediction were investigated. Then, a B cell epitope was analyzed using Immune Epitope Database, which predicts the target region and helps in vaccine development.Results: PorB is a surface-exposed protein comprising 340 amino acids and frequently appears (61.76%) as a random coiled structure. PorB was present outside the cell and the maximum length of the predicted epitope was from amino acids 91–108, i. e., 18 amino acids long. This epitope can be considered for designing Abs and vaccines against C. trachomatis.Conclusion: Although many attempts have been made to develop a vaccine against C. trachomatis, no protective vaccines are available to date. More detailed studies focusing on PorB should be performed to design vaccines against C. trachomatis because of the presence of different immunization protocols and requirement of different protective mechanisms.
Keywords: chlamydia trachomatis; in silico; PorB; vaccine design